Clinical Evaluation of a Disposable Artificial Kidney. Issue 5668 (23rd August 1969) - Kulatilake, A. E.; Vickers, J.; Shackman, R.
Abstract : The in-vivo performance of a new disposable parallel flow countercurrent type of artificial kidney has been compared with that of the modified four-layered Kiil dialyser. The dialysance of urea and endogenous creatinine in the former was significantly better than in the latter for similar blood flow rates, and, moreover, unlike the dialysance with the Kiil dialyser it continued to improve over 12 hours. Among 100 disposable artificial kidneys tested no failure occurred from blood leaks despite the use of high negative pressures in the dialysate compartment. No pyrogen reactions were observed. These new artificial kidneys were ready for use in less than one-seventh of the time taken to prepare the conventional Kiil dialyser. Other advantages are their low priming volumes, the lack of a pump in the blood line, and the reduced risk of infection.